Valuasi Ekonomi Objek Wisata Dermaga Kereng Bangkirai Sungai Sebangau Kota Palangka Raya - John Terry; Abdul Mukti; Revi Sunaryati (Journal of Environment and Management, 2020)
The purpose of this study was to analyze the economic valuation of tourism objects at the Kereng Bangkirai Pier, Sebangau River, Palangka Raya City. It also analyzes the willingness to pay (WTP) as public participation to manage the tourism object of Kereng Bangkirai Pier. The respondents grouped into two categories, namely tourists/visitors and the community around the site; each consist of 28 persons. The results show that the WTP value is 1.633726273, which is ranged from 1 to 2 value. The real WTP falls in the second range (Rp. 5.000,00-Rp. 7.000,00 per person), or Rp. 6.300,00 per visitor precisely. The variables influencing the PAPs value are age: (-0.368814), education (-0.514952), tourist attraction (-3.599377), site cleanness (-1.181992), and satisfaction with tourist attraction (-0.261969).